Introducing entrepreneurship into the public university scheme in Egypt - Abbas, Ahmed (AUC Knowledge Fountain, 2016)
The overall study of available literature regarding entrepreneurship in Egypt reveals several gaps and barriers in the ecosystem. Human Capital represented in: education institutions, availability of skilled labor, and culture norms come at the forefront. Absence of entrepreneurship in the educational curricula in schools and most universities is a contributing factor of t the lagging entrepreneurship activities. This research investigates, explains and analyzes the existing situation of entrepreneurship, specifically social entrepreneurship in colleges of commerce in Egyptian public universities. Colleges of commerce are chosen for being the natural home of entrepreneurship education. Description and evaluation of the status quo are employed to explicitly understand the symptoms and causes of this gap. Also, it creates a roadmap of the mechanics, procedures, key players and motivations required to introduce a new curriculum in the existing system. Understanding the universities and colleges’ bylaws and regulations as well as supporting and supervising institutions - like the Supreme Council of Universities SCU and its supreme sub-councils - serves in designing an intervention applicable and compliant with the existing official and institutional framework. The study involves primary and secondary data collection and analysis. Quasi-structured interviews with business professors in several public universities in Egypt were conducted to reveal the existing status quo, engage stakeholders, and collect data and feedback as well as recommendations introducing entrepreneurship to the public university. Secondary data was used to build on existing researches and findings about the Egyptian context. In addition, I study the evolution and development of social entrepreneurship curricula in some universities to come up with best practices and lesson-learned applicable to the Egyptian context. According to Ajzen theory of Planned Behavior as well as several researches, education is proved to cause both behavioral and cultural changes Students who were exposed to some entrepreneurship and social entrepreneurship education were more inclination to start their own entrepreneurial endeavors, as opposed to being employed by others. Egypt has a large untapped resource of 325,400 annual graduates of Public Universities (CAPMAS 2013); of which 78,625 graduate of faculties of commerce with different majors. College graduates lack both the knowledge and the skill-set for entrepreneurship 5 and social entrepreneurship. There are no academic courses, majors or minors on undergraduate nor graduate levels for entrepreneurship or social entrepreneurship, with 2 exceptions of Helwan and Zagazig Universities. The only available course is Management of Small and Medium Enterprises. this is limited to senior management students. Despite the bureaucracy and stagnation of public universities in Egypt, there is a clear opportunity of change, given the size and distribution of public universities that can contribute to poverty alleviation and job creation - if steered towards social entrepreneurship. Existing bylaws and procedures dictate the start approval process from department level to the college to the dean to the head of the university and ultimately approval from the SCU. Each university and college has independent bylaws; however, introducing new curricula mirrors existing curricula in local universities. New curricula will cut quotas of existing professors and may face serious objections by traditional professors. The SCU has agreed to make entrepreneurship major curricula in universities, as advertised on February 2015. This could be perceived as a beckoning call for implementation by all public universities. Recommended intervention suggests engagement of management professors, SCU, and NGOs like Nahdit El Mahrousa, Alshanek Ya Balady, Ashoka, Injaz as well as development institutions like UNDP in a collaborative project to pilot new curricula at a selective number of faculties of commerce. The new course should be introduced as a basic course to senior undergraduates and graduate students. Eventually, other faculties can implement programs using the pilot faculties. Following the development model of international universities, further steps should expand this initiative by offering majors and minors in social entrepreneurship on both undergraduate and graduate levels. It is advised that these courses be offered in in Arabic to ensure reaching a larger segment of students. On the graduate levels, initiating a new diploma on social entrepreneurship would be much easier and will not overlap with existing programs. However, these diplomas should be open to all students regardless of their undergraduate majors.